Benef??cios da implanta????o do ERP na ??rea financeira dos Correios: um estudo de caso - Caldeira, Marcos Tarc??sio Campos (2016)
The main objective of this research is to identify the benefits of an ERP system implementation in the Finance Department for a public company. The theoretical foundation was based on literature review and relevant publications on ERP implementation, with emphasis on the benefits from this implementation. The survey consists of a single case study in a postal services company, Correios, conducted with the use of quantitative and qualitative approaches, interviews with users and functional coordinators involved in business areas and with the coordinators in technology area responsible for the migration of legacy systems. The analysis of the ERP implementation project documentation, procurement contracts and audits carried out by external oversight bodies also supported the survey. As results, the study identified benefits in the domain of decision making information quality, order revenue management of 17 billion / year and reduction of 1,180 job posts in the financial area, assuring the confidence and maturity in the creation of Shared Services Centers for the postal enterprise.